Reactions of Di(Alkoxy) Dichlorooxotungsten(VI) with 2,2’-Bipyridyl - Dabas, P.; Rastogi, M.K. (Asian Journal of Chemistry, 2010)
All the di(alkoxy) dichlorooxotungsten(VI) complexes give bipyridyldichlorooxo-tungsten(IV) on treatment with 2,2´-bipyridyl in alcohol/benzene medium. The two alkoxy groups are knocked off and the oxidation state of tungsten is reduced from (VI) to (IV). The resulting compound is one and the same is confirmed by IR and UV spectra, and other physical data.